Translating emotion-related metaphors: A cognitive approach - Hanić Jasmina; Pavlović Tanja; Jahić Alma (ExELL (Explorations in English Language and Linguistics))
The paper explores the existence of cognitive linguistics principles in translation of emotion-related metaphorical expressions. Cognitive linguists (Lakoff & Johnson, 1980; Lakoff, 1987) define metaphor as a mechanism used for understanding one conceptual domain, target domain, in terms of another conceptual domain, source domain, through sets of correspondences between these two domains. They also claim that metaphor is omnipresent in ordinary discourse. Cognitive linguists, however, also realized that certain metaphors can be recognized and identified in different languages and cultures whereas some are language- and culture-specific. This paper focuses on similarities and variations in metaphors which have recently become popular within the discipline of Translation Studies. Transferring and translating metaphors from one language to another can represent a challenge for translators due to a multi-faceted process of translation including both linguistic and non-linguistic elements. A number of methods and procedures have been developed to overcome potential difficulties in translating metaphorical expressions, with the most frequent ones being substitution, paraphrase, or deletion. The analysis shows the transformation of metaphorical expressions from one language into another and the procedures involving underlying conceptual metaphors, native speaker competence, and the influence of the source language.